1999
DOI: 10.1034/j.1600-0501.1999.100604.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic features of trabecular bone in edentulous maxillae

Abstract: Following tooth loss, the maxillary alveolar ridge is affected by extensive resorption and its cancellous bone substance undergoes intense remodeling processes. This is particularly important for endosseous implant surgery as the primary stability and thus the prognosis of endosseous implants depends on the cancellous bone density and structure of the alveolar ridge. To analyze the structure of alveolar trabecular bone, 156 sections were obtained from 52 edentulous maxillae (29 female, 23 male; mean age: 72.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
82
2
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 0 publications
11
82
2
4
Order By: Relevance
“…Only the region of the first molar assessed by Ulm et al (1999) presented a higher bone volume fraction compared with our 'posterior' results, which is presumably due to the inclusion of the maxillary tuberosity in the VOI in this study. Both, histology and microCT, represent standard techniques for bone quality evaluation.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…Only the region of the first molar assessed by Ulm et al (1999) presented a higher bone volume fraction compared with our 'posterior' results, which is presumably due to the inclusion of the maxillary tuberosity in the VOI in this study. Both, histology and microCT, represent standard techniques for bone quality evaluation.…”
Section: Discussioncontrasting
confidence: 43%
“…Comparison of the results on maxillary trabecular bone quality with previous histological data ( Ulm et al, 1999) confirmed a decreasing quality from anterior to posterior regions, but the values of the present study were in general slightly higher (i.e., minor differences for bone volume fraction and more distinct differences for trabecular thickness, separation, and number). Only the region of the first molar assessed by Ulm et al (1999) presented a higher bone volume fraction compared with our 'posterior' results, which is presumably due to the inclusion of the maxillary tuberosity in the VOI in this study.…”
Section: Discussionmentioning
confidence: 36%
See 2 more Smart Citations
“…The alveolar bone is a skeletal part that is dependent on the presence of teeth and masticatory function, since, in the absence of teeth [2] or lack of mechanical stimulation transmitted by implant supported overdenture, it undergoes disuse atrophy [3]. Independently of the age, there is a great inter-individual variation in trabecular volume and interconnections, leading to variable trabecular bone patterns [4]. Variation in the trabecular bone microstructure is also sitedependent within individuals [5,6].…”
Section: Introductionmentioning
confidence: 99%